Underground empire : how America weaponized the world economy - Farrell, Henry, 1970-; Newman, Abraham, 1973- (Henry Holt and Company, 2023)
"A deeply researched investigation that reveals how the United States is like a spider at the heart of an international web of surveillance and control, which it weaves in the form of globe-spanning networks such as fiber optic cables and obscure payment systems America's security state first started to weaponize these channels after 9/11, when they seemed like necessities to combat terrorism--but now they're a matter of course. Multinational companies like AT&T and Citicorp build hubs, which they use to make money, but which the government can also deploy as choke points. Today's headlines about trade wars, sanctions, and technology disputes are merely tremors hinting at far greater seismic shifts beneath the surface. Slowly but surely, Washington has turned the most vital pathways of the world economy into tools of domination over foreign businesses and countries, whether they are rivals or allies, allowing the U.S. to maintain global supremacy. In the process, we have sleepwalked into a new struggle for empire. Using true stories, field-defining findings, and original reporting, Henry Farrell and Abraham Newman show how the most ordinary aspects of the post-Cold War economy have become realms of subterfuge and coercion, and what we must do to ensure that this new arms race doesn't spiral out of control"--